The Memory of the Stones - Holy Places in Early Medieval Croatia - Jurković, Miljenko (Array, 1996)
The topic of the round table is discussed from sociological, philosophical, cultural and historical point of view. The author tries to picture holy places on well documented material - monuments of Early Medieval Croatian state - on both points of view: from today's historical panorama as well as from the historical conspectus of the time to which they belong.